The Aga Khan Rural Support Programme : a journey through grassroots development. - Shoaib, Sultan Khan (Karachi, Oxford University Press, 2009)
This title is a narration of participatory development experience in the rural areas of South Asia. It is meant for both the professional and lay reader interested in poverty alleviation and rural development.
Include Bibliography Reference and Index Material.
Keywords: Aga Khan Rural Support Programme (Pakistan); Developing countries; Rural development Developing countries